THE OPTIMIZATION OF SINGLE WINDOW OR SSWALFA E-GOVERNMENT SERVICES IN MAKING LICENSE IN GUNUNG ANYAR KELURAHAN, SURABAYA - Anggun Puspitaningrum; Achluddin Ibnu Rochim; Adi Susiantoro (Universitas 17 Agustus 1945 Surabaya, 2023)
Basically the implementation of technology-based public services to the community is very important. The problem in this study is that there are still many people who do not know and do not understand how this technology-based service is due to frequent problems when charging and frequent service problems that often experience problems so that people cannot log in to enter data. The purpose of this research is to see the effectiveness of public services in the E-Government program and what are the obstacles in optimizing the use of websites in an effort to improve services. This research method is descriptive using a qualitative approach. This data analysis technique is data collection, data reduction, data presentation, and conclusion drawing. The results of this study are that the use of the website has not been optimally implemented due to (1) the new policy with a different service system makes the community unfamiliar (2) the lack of socialization that is carried out means that there are still people who do not know about the service system using the website so that it creates a lack of public understanding on the use of the website and (3) the lack of quality human resource capabilities makes many people feel helpless.